(3GdebOeI GdCLQhejI aj Yde GdYQHjIs - (3GdUfgGLj, GHf BLQhe, CHh YHO Gddg, eMeO Hf YHO Gddg Hf OGhO, (B723 (3g`s ((3eMeO Hf MGLj YHO GdQMje CafOj GdbTdGbjs)
(3ChdgG (B:s
(3GdcdGe gh GddaX GdeQcH GdeajO HGdhVY hCbSGeg KdGKI(B: (3GSe haYd hMQa LGA deYfi, aGdGSe jYQa HGdNaV hGdJfhjf hONhd GdCda hGddGe hMQha GdNaV hgj ef hEdi hYf hYdi haj hQH hGdHGAs
(3BNQgG (B:s
(3hCeG eG jNaV HGdEVGaI fMh bhdc ZdGe RjO hgh Ydi bSejf eG jJbOQ HGddGe fMh ZdGe RjO hHeG jbOQ fMh bhdc KhH NR hHGH SGL heG CTHg Pdc hGddg CYde HGdUhGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 7 / 33s
(3eYLe GdeDdajf(B: 3 / 641s
(3cTa GdXfhf(B: 2 / 1796s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdfMhs